(untitled) (Journal of the College of Basic Education, 2022)
Been studied the effect of hot alcoholic extract of the plant Cymbopogon citratus on the growth of some gram-negative nature bacteria like Klebsiella pneumonia, E. coli, and gram- positive bacteria like Staphylococcus aureus by using the agar well diffusion method best inhibitory zone (23.0 mm) on the growth of S. aureus and the lowest inhibitory zone for the hot alcoholic extract on growth of E. Coli.